The remarkable record of Job the ancient wisdom, scientific accuracy and life-changing message of an amazing book - Morris, Henry Madison, 1918- (Green Forest, AR Master, 2000)
Includes bibliographical references and indexes.
Keywords: Bible. O.T. Job -- commentaries